Choroidal Thickness Measurement in Systemic Lupus Erythematosus Patients with or Without Ocular Manifestation - Khadka, Prajita; Kharel (Sitaula) , Ranju; Mishra, Sanjeeb Kumar; Jha, Saket; Lamichhane, Srijana; Gyawali, Parash; Chandan, Aayush (Journal of Nepal Health Research Council, 2024)
Background: Systemic Lupus Erythematosus is a multi-systemic disease that has a high morbidity rate. Choroids usually have a distinct structural makeup in different systemic disorders which makes it easier to be used as a potential tool for the study of disease activity. Methods: This study was an observational cross-sectional prospective study with a total of 51 Systemic Lupus Erythematosus patients and 51 normal controls were included. The choroidal thickness values were determined using the Spectralis Spectral Domain Optical Coherence Tomography instrument (Heidelberg Engineering). Results: The results showed that the mean subfoveal, nasal, and temporal choroidal thickness in Systemic Lupus Erythematosus patients with ocular manifestations had thinner choroidal thickness compared to normal controls with p<0.001, p=0.008, and p<0.001, respectively. On the other hand, Systemic Lupus Erythematosus patients without ocular manifestations had relatively thicker subfoveal choroidal thickness compared to normal controls (p<0.001) but nasal and temporal choroidal thickness were not statistically significant (p=0.264 and p=0.347 respectively). Conclusions: The findings suggested that choroidal thickness measurement may serve as an indicator of disease activity and prognosis in Systemic Lupus Erythematosus patients, as well as a potential tool to predict the occurrence of ocular manifestations. Thinning of the choroid may be associated with factors such as decreased blood flow leading to atrophy or chronic inflammation, while thickening of the choroid may indicate active stage of the disease and the possibility of severe ocular manifestations in the future. Keywords: Choroidal thickness; SLE; spectral-domain optical coherence tomography; ocular manifestation.